Perlindungan Hukum Terhadap Pemain Sepak Bola yang Dicederai oleh Pemain Lawan Secara Sengaja dalam Pertandingan Sepak Bola - Alffian Andhika Fahlefi; Riky Rustam (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
In football matches, there are often serious violations caused by the high and heated tension of the match. The high and heated tension sometimes causes losses for players, for example, there are players who are injured by opposing players in football matches. The problem studied is regarding the liability of players who injure other players in football matches and legal protection for football players who are intentionally injured in football matches. This research was conducted normatively through a legislative and conceptual approach. Based on the results of this study, it can be concluded that injuring other players is an unjustifiable act, both under lex sportiva and positive law, in addition, injured players also receive legal protection under lex sportiva and positive law and can file a lawsuit for unlawful acts. The government should make a clear separation of regulations between lex sportiva and positive law so that there is no overlap between lex sportiva and positive law and football players must be more careful and not take actions to injure other players. The referee must also be firm when football players start to commit serious violations.